2012
DOI: 10.1128/jb.06812-11
|View full text |Cite
|
Sign up to set email alerts
|

CovR Alleviates Transcriptional Silencing by a Nucleoid-Associated Histone-Like Protein in Streptococcus mutans

Abstract: In Streptococcus mutans, the global response regulator CovR plays an important role in biofilm formation, stress tolerance response, and caries production. We have previously demonstrated that CovR activates a large gene cluster, which is a part of a genomic island, TnSmu2. In this article, we have further characterized CovR at the molecular level to understand the gene activation mechanism. Toward this end, we mapped the transcription start site of the operon that lies upstream of the SMU.1348 gene (P SMU.134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…In addition to strain differences in gene content, our high-resolution analysis revealed the important role that mobile elements have in the variability of the CovR transcriptomes (21, 25, 26). Previously, CovR has been proposed to silence a large genomic island in Streptococcus mutans (57). Notably, the S. mutans CovR is an orphan regulator which has lost its cognate histidine kinase CovS and, consequently, the CovR function is independent of its phosphorylation (57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to strain differences in gene content, our high-resolution analysis revealed the important role that mobile elements have in the variability of the CovR transcriptomes (21, 25, 26). Previously, CovR has been proposed to silence a large genomic island in Streptococcus mutans (57). Notably, the S. mutans CovR is an orphan regulator which has lost its cognate histidine kinase CovS and, consequently, the CovR function is independent of its phosphorylation (57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pIB-B39 contains the hlp gene from S. mutans, which was cloned into NdeI and XhoI sites to produce C-terminally His-tagged HLP (Biswas & Mohapatra, 2012). The plasmid was transformed into E. coli BL21(DE3)/pLysS cells and the production of HLP-His was induced by the addition of isopropyl -d-1-thiogalactopyranoside (IPTG).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…In contrast to E. coli HU, streptococcal HLP is essential for survival (Bugrysheva et al, 2011;; therefore, it is a potential target for drug development. Streptococcal HLP bind to DNA nonspecifically, although certain streptococcal HLPs have a preference for AT-rich DNA Biswas & Mohapatra, 2012). We and other researchers have also shown that streptococcal HLP also participates in gene transcription by binding to the target DNA (Liu Crystals of SmuHLP obtained from Wizard 1 condition A5.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of streptococcal HLP to heart and kidney basement membranes was also reported and it was found to be highly immunogenic [10]. But unlike HU of E. coli, streptococcal HLP was shown to be essential for the survival of the pathogen [13,14]. Due to these reasons, streptococcal HLP is considered as a potential drug target.…”
Section: Introductionmentioning
confidence: 99%